2022
DOI: 10.1210/clinem/dgac005
|View full text |Cite|
|
Sign up to set email alerts
|

Discriminative Capacity of CT Volumetry to Identify Autonomous Cortisol Secretion in Incidental Adrenal Adenomas

Abstract: Context Incidentally discovered adrenal adenomas are common. Assessment for possible autonomous cortisol excess (ACS) is warranted for all adrenal adenomas given the association with increased cardiometabolic disease. Objective To evaluate the discriminatory capacity of three-dimensional volumetry on computed tomography (CT) to identify ACS. Design, Setting, Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…found a negative linear correlation between limb width of the contralateral adrenal gland and cortisol levels after DST in patients with unilateral adrenal adenomas ( 18 ). Another study showed the significance of the volume of adrenal adenomas and contralateral adrenal glands associated with cortisol secretion ( 19 ). In our study, we found that patients with MACS had thinner contralateral adrenal compared with NFAT.…”
Section: Discussionmentioning
confidence: 99%
“…found a negative linear correlation between limb width of the contralateral adrenal gland and cortisol levels after DST in patients with unilateral adrenal adenomas ( 18 ). Another study showed the significance of the volume of adrenal adenomas and contralateral adrenal glands associated with cortisol secretion ( 19 ). In our study, we found that patients with MACS had thinner contralateral adrenal compared with NFAT.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal lesion was confirmed as an adenoma using attenuation criteria <10 Hounsfield units (HU) in unenhanced images or strict washout criteria when delayed contrast images were available (relative washout >40% and/or absolute washout >60%). 1,15 When magnetic resonance imaging (MRI) was available, signal drop on out-of-phase images was considered diagnostic of an adenoma. When these methods were not available or diagnosis was unclear, confirmatory CT using a standard adrenal protocol was performed (noncontrast imaging, 70-second post-contrast venous phase imaging, and 10- to 15-minute delayed post-contrast phase), using known density and washout criteria for adenoma diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The Program for Adrenal Disorders at our institution has implemented a systematic hormonal assessment for all adrenal incidentalomas, as previously described. 14,15 On the first day, blood samples were obtained between 08:00 and 09:00, after an 8-hour overnight fast, for measurement of seated plasma aldosterone concentration (PAC), plasma renin activity (PRA) and/or direct renin concentration (DRC), ACTH, serum creatinine, sodium and potassium. All patients submitted a 24h urine collection to measure urinary aldosterone, cortisol, cortisone and sodium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations